ANALISIS KOMUNIKASI KESEHATAN BIDAN DESA DALAM UPAYA PENCEGAHAN STUNTING - Maielayuskha Maielayuskha; Ardiyansyah Ardiyansyah (Universitas Muhammadiyah Jember, 2021)
The health of pregnant women, infants and toddlers are one of the most influential factors in the welfare of society in Indonesia, especially in rural areas. Currently, one of the health problems in rural areas that is becoming a significant concern is stunting. In reducing this problem, communicators are needed to convey the information related to children's height is shorter than their age to villagers with babies, toddlers, and pregnant women. The village midwives are the communicators who have an essential role in providing information services to the villagers. They use persuasion techniques to increase the quality and quantity of the delivered message. This research was conducted at the Polindes in Baru Village, Maro Sebo District, Muaro Jambi Regency. Through qualitative research, the researcher describes two health communication persuasion techniques used by village midwives. First, the intensification tactic is through the repetition of messages about nutritious food for infants and toddlers to avoid and reduce stunting. This tactic is conducted through counselling activities to the villagers' homes during Covid-19. Second, the omission tactic is through the delivery of subtle messages using the local language with the aim that critical messages can cover subtle messages through spoken words. The village midwife's health communication process obstacle is that health workers do not play their role as communicators in conveying information about stunting.